Cooperation or competition – When do people contribute more? A field experiment on gamification of crowdsourcing. Issue 127 (July 2019) - Morschheuser, Benedikt; Hamari, Juho; Maedche, Alexander
Highlights: Field experiment on competitive, cooperative, and inter-team competitive gamification. Intrinsic motivation, contribution and WOM highest in inter-team competition. Users organized into teams rather than as individual is more optional structure. Abstract: Information technology is being increasingly employed to harness under-utilized resources via more effective coordination. This progress has manifested in different developments, for instance, crowdsourcing (e.g. Wikipedia, Amazon Mechanical Turk, and Waze), crowdfunding (e.g. Kickstarter, Indiegogo, and RocketHub) or the sharing economy (e.g. Uber, Airbnb, and Didi Chuxing). Since the sustainability of these IT-enabled forms of resource coordination do not commonly rely merely on direct economic benefits of the participants, but also on other non-monetary, intrinsic gratifications, such systems are increasingly gamified that is, designers use features of games to induce enjoyment and general autotelicy of the activity. However, a key problem in gamification design has been whether it is better to use competition-based or cooperation-based designs. We examine this question through a field experiment in a gamified crowdsourcing system, employing three versions of gamification: competitive, cooperative, and inter-team competitive gamification. We study these gamified conditions' effects on users' perceived enjoyment and usefulness of the system as well as on their behaviors (system usage, crowdsourcing participation, engagement with the gamification feature, and willingness to recommend the crowdsourcing application). The results reveal that inter-team competitions are most likely to lead to higher enjoyment and crowdsourcing participation, as well as to a higher willingness to recommending a system. Further, the findings indicate that designers should consider cooperative instead of competitive approaches to increase users' willingness to recommend crowdsourcing systems. These insights add relevant findings to the ongoing discourse on the roles of different types of competitions in gamification designs and suggest that crowdsourcing system designers and operators should implement gamification with competing teams instead of typically used competitions between individuals.